Exploring Media Attention Toward Pandemics and Health Crisis in Cameroon: A Comparative Content Analysis of Cameroon Tribune, The Guardian Post, and Le Jour Newspapers Coverage of COVID-19 - Moki, Stephen Mokondo; Kome, Slesor Ebane; Ngange, Kingsley Lyonga (Advances in Social Sciences Research Journal, 2026)
The purpose of this study was to examine which Cameroon newspaper (Cameroon Tribune, The Guardian Post, and Le Jour) paid more attention in reporting the COVID-19 pandemic. A quantitative content analysis was used to examine the content of these newspapers with the agenda-setting theory as a theoretical guide. The findings reveal that out of a total of 2575 stories on COVID-19, Cameroon Tribune reported 49.4%, as opposed to 29.2% and 21.4% for The Guardian Post and Le Jour newspapers, respectively. However, The Guardian Post gave more prominence and visibility to the pandemic by publishing more stories on premium pages (front pages and pages 2 & 3) and using more banner headlines. It was also noticed that the newspapers carried fewer in-depth reports. A greater proportion (39.6%, 29.9% and 20.5%) of COVID-19 mentions were just a ¼ page, half page and less than ¼ page, respectively. Generally, the newspapers played their social responsibility role by frequently mentioning the pandemic in their different editions, thereby creating awareness of the existence of this health pandemic. However, it is recommended that the media should, in future, not only focus on mentioning health pandemics in their reports but should give them more prominence and visibility by placing them on the front pages and using banner headlines to catch readers' attention. Similarly, the media should consider giving more in-depth coverage on health pandemics like COVID-19. Less in-depth stories are often scanty and lack scientific details.